A study on the prevalence and related factors of frailty and pre-frailty in the older population with hypertension in China: A national cross-sectional study - Zeng, Xue-zhai; Jia, Na; Meng, Ling-bing; Shi, Jing; Li, Ying-ying; Hu, Jia-bin; Hu, Xing; Li, Hui; Xu, Hong-xuan; Li, Jian-yi; Qi, Xin; Wang, Hua; et al. (Frontiers in Cardiovascular Medicine, 2023)
Objective: To explore the prevalence and factors associated with frailty and pre-frailty in elderly Chinese patients with hypertension. Background: In China, there have been few national studies into the prevalence and factors associated with frailty and pre-frailty in elderly patients with hypertension. Methods: Through the 4th Sample Survey of Aged Population in Urban and Rural China (SSAPUR) in 2015, the situation of hypertension subjects aged 60 years or older in 31 provinces, autonomous regions, and municipalities in mainland China was obtained. And the frailty index was constructed based on 33 potential defects, elderly hypertensive patients are classified as robust,, frailty, and pre-frailty. Results: 76,801 elderly patients with hypertension were enrolled in the study. The age-sex standardised prevalence of frailty and pre-frailty in hypertensive elderly in China was 16.1% (95%CI 15.8%-16.3%), 58.1% (95%CI 57.7%-58.4%). There were significant geographical differences in the prevalence of frailty and pre-frailty in elderly hypertensive patients. Multinomial logistic regression analysis showed that poor economic status, activities of daily living disability, and comorbid chronic diseases were related to frailty and pre-frailty. Conclusion: Frailty and pre-frailty are very common in elderly Chinese patients with hypertension and have similar risk factors. Prevention strategies should be developed to stop or delay the onset of frailty by targeting established risk factors in the pre-frailty population of elderly hypertension. It is also crucial to optimize the management of frailty in elderly Chinese patients with hypertension.